Therapeutic effect of berberine on TDP-43-related pathogenesis in FTLD and ALS. Issue 1 (December 2016) - Chang, Cheng-Fu; Lee, Yi-Chao; Lee, Kuen-Haur; Lin, Hui-Ching; Chen, Chia-Ling; Shen, Che-Kun; Huang, Chi-Chen
Abstract Background In the central nervous system regions of the sporadic and familial FTLD and ALS patients, TDP-43 has been identified as the major component of UBIs inclusions which is abnormally hyperphosphorylated, ubiquitinated, and cleaved into C-terminal fragments to form detergent-insoluble aggregates. So far, the effective drugs for FTLD and ALS neurodegenerative diseases are yet to be developed. Autophagy has been demonstrated as the major metabolism route of the pathological TDP-43 inclusions, hence activation of autophagy is a potential therapeutic strategy for TDP-43 pathogenesis in FTLD and ALS. Berberine, a traditional herbal medicine, is an inhibitor of mTOR signal and an activator for autophagy. Berberine has been implicated in several kinds of diseases, including the neuronal-related pathogenesis, such as Parkinson's, Huntington's and Alzheimer's diseases. However, the therapeutic effect of berberine on FTLD or ALS pathology has never been investigated. Results Here we studied the molecular mechanism of berberine in cell culture model with TDP-43 proteinopathies, and found that berberine is able to reverse the processing of insoluble TDP-43 aggregates formation through deregulation of mTOR/p70S6K signal and activation of autophagic degradation pathway. And inhibition of autophagy by specific autophagosome inhibitor, 3-MA, reverses the effect of berberine on reducing the accumulation of insoluble TDP-43 and aggregates formation. These results gave us the notion that inhibition of autophagy by 3-MA reverses the effect of berberine on TDP-43 pathogenesis, and activation of mTOR-regulated autophagy plays an important role in berberine-mediated therapeutic effect on TDP-43 proteinopathies. Conclusion We supported an important notion that the traditional herb berberine is a potential alternative therapy for TDP-43-related neuropathology. Here we demonstrated that berberine is able to reverse the processing of insoluble TDP-43 aggregates formation through deregulation of mTOR/p70S6K signal and activation of autophagic degradation pathway. mTOR-autophagy signals plays an important role in berberine-mediated autophagic clearance of TDP-43 aggregates. Exploring the detailed mechanism of berberine on TDP-43 proteinopathy provides a better understanding for the therapeutic development in FTLD and ALS.